From hunting to photography. Cult of territorial deities and individualistic ethics within the dynamic of environmental interactions - Théophile Johnson (European Bulletin of Himalayan Research)
This article examines shifting environmental interactions and divinity beliefs in Manang (Nepal). It shows how significant findings emerge regarding the impact of the ban on hunting. The former prominence of the local deity Dorje Legpa has been undermined due to religious and political transitions. The research notes how former rituals, such as Paten, were uprooted by the syncretisation of local deities with Buddhist figures, paralleling a shift from community sacrifices to individual morality. This transition culminates in present-day Manang with the Syakumbre festival that promotes non-violence and assimilates the yogic ascetic Milarepa as a new figure of worship. As indigenous knowledge declines, particularly among younger generations, wildlife populations such as those of bharals and panthers proliferate and present changed behaviour. And the ban on hunting triggers certain creative cultural responses. Some young people turn to photography to both document wildlife and reimagine their community bonds with other species. The underlying narrative is a complex tapestry of cultural, religious and environmental threads where evolved Buddhist ethos, shifts in local power constructs and transformed relationships with non-human entities are interwoven. This multifaceted case illustrates how a strict hunting ban propels a community towards new forms of expression and understandings, encapsulating the broader historical trajectory of Manang’s socio-environmental relations.